Ultrasound assessment of gastric emptying time after a standardised light breakfast in healthy children: A prospective observational study. Issue 12 (December 2018) - Beck, Christiane E.; Witt, Lars; Albrecht, Lisa; Dennhardt, Nils; Böthig, Dietmar; Sümpelmann, Robert
Abstract : OBJECTIVES: Current guidelines recommend 6 h of fasting for solids before anaesthesia. However, prolonged fasting may lead to discomfort, hunger, thirst, misbehaviour and lipolysis. To prevent this, a more liberal fasting regimen has been empirically implemented in our children's hospital, allowing a shorter fasting time of 4 h for a standardised light breakfast. AIM: The aim of this study was to determine the gastric emptying time after a standardised light breakfast in healthy children. DESIGN: A prospective observational noninterventional study. METHODS: After fasting overnight, the children had a standardised light breakfast. Before and afterwards, ultrasound examinations of the gastric antrum were performed hourly to determine the gastric antral area (GAA), which is a surrogate parameter for gastric volume in children in the right lateral position (RLP). Demographic data and fasting times are presented as mean ± SD (range) and GAA as median (interquartile range). RESULTS: Twenty-two children aged 7.8 (2.5 to 13.6) years volunteered for this study. After fasting overnight [735 ± 120 (467 to 930) min], the initial GAA was 3.06 (2.35 to 4.03) cm 2 in RLP. After the light breakfast, GAA in RLP initially increased and decreased subsequently. After 4 h, GAA in RLP was lower than the initial value (median of differences −0.54, 95% confidence interval −1.00 to −0.07, P  < 0.05). Correlation between GAA in RLP and fasting time was significant ( r  = −0.62, P  < 0.0001). Using a linear regression model, the calculated mean gastric emptying time after the standardised light breakfast was 211 min for GAA = 3.06 cm 2 . CONCLUSION: The study showed a mean gastric emptying time of less than 4 h after a standardised light breakfast in children. These results encourage our current clinical practice and support the efforts towards a more liberal fasting regimen for light meals in paediatric anaesthesia. TRIAL REGISTRATION: German Registry of Clinical Studies (DRKS-ID: DRKS 00013893).